2009
DOI: 10.3899/jrheum.090066
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Transcription Factor RORC2 Is Inversely Correlated with FOXP3 Expression in the Joints of Children with Juvenile Idiopathic Arthritis

Abstract: We demonstrated for the first time an increased synovial expression of the transcription factor of Th17, RORC2, in JIA, and its inverse relationship with FOXP3 mRNA. These results extend research on "Th17" and Tregs in JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 56 publications
4
20
1
3
Order By: Relevance
“…These findings are partially in agreement with the results reported in other investigations (22)(23)(24), in which increased levels of IL-17A, IL-17A-producing cells, and RORC have been demonstrated in the SF of children with JIA. In addition, we also observed an enrichment for CD4ϩCD161ϩ T cells in the JIA SF, the majority of which exhibited either the Th17/Th1 phenotype or the nonclassic Th1 (RORCϩIFN␥ϩIL-17Ϫ) phenotype.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are partially in agreement with the results reported in other investigations (22)(23)(24), in which increased levels of IL-17A, IL-17A-producing cells, and RORC have been demonstrated in the SF of children with JIA. In addition, we also observed an enrichment for CD4ϩCD161ϩ T cells in the JIA SF, the majority of which exhibited either the Th17/Th1 phenotype or the nonclassic Th1 (RORCϩIFN␥ϩIL-17Ϫ) phenotype.…”
Section: Discussionsupporting
confidence: 83%
“…T cell infiltrates predominantly consist of Th1-skewed cells, which were thought to have a central role in disease pathogenesis (21). After the association between Th17 cells and several human autoimmune diseases, including RA, was observed, some studies found increased levels of IL-17A, as well as the presence of Th17 cells and the expression of their transcription factor, RORC, in the synovial fluid (SF) of children with JIA (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Previous studies have shown that IL-17-producing cells are enriched in the synovial fluid of children with extended oligoarthritis compared with patients with persistent oligoarthritis in a reciprocal relationship with regulatory T cells (Treg) [8]. An inverse relationship between the increased synovial expression of the Th17 transcription factor RORC2 and the Treg transcription factor FOXP3 has also been demonstrated in joints of children with JIA [12].…”
Section: Introductionmentioning
confidence: 85%
“…2). Interestingly, Treg in the blood of children with O-JIA appear to be present at normal or even decreased frequency, compared with healthy children (Refs 3, 79,80). In an early study of the very severe form of JIA known as systemic JIA (sJIA; a form of disease where in addition to arthritis, patients display systemic symptoms such as fever, rash and major organ involvement), Treg were shown to be reduced in peripheral blood in severe active disease, just before autologous stem cell transplantation.…”
Section: Biology Of Treg In Juvenile Arthritismentioning
confidence: 99%